A new species, new synonymy, and notes on Neomacrocoris (Heteroptera: Nepomorpha: Naucoridae) - Sites, Robert W. (Zootaxa, 2015)
Based on borrowed museum specimens and fresh collections from South Africa, Tanzania, and Uganda, many specimens of Neomacrocoris Montandon have been made available for study. Neomacrocoris liberianus n. sp. is described from Liberia and Sierra Leone based on two museum specimens. Neomacrocoris bondelaufa Sites is synonymized with N. transvaalensis (Distant) and distribution records for N. parviceps Montandon and N. vuga Sites are provided.